Greek Captives and Mediterranean Slavery, 1260–1460 - Grant, Alasdair C. (Edinburgh University Press, 2025)
Captivity and enslavement were characteristic experiences of Greek Christians in the late medieval Mediterranean. During this time, Muslim Turks and Christian western Europeans conquered and traded at the expense of the shrinking Byzantine Empire. By bringing together literary and documentary sources spanning a geographical canvas from the Aegean to Egypt and from Cyprus to Catalonia, this book tells that story in full for the first time. It traces this crisis of captivity from its origins in thirteenth-century Asia Minor to its explosion into a Mediterranean-wide phenomenon, interrogating different types of unfreedom and forced movement and evaluating their significance for Greeks’ religious and diplomatic relationships with their neighbours, both Christian and Muslim. This book tells the story of thousands of ordinary people caught up in conflict and dispersed across the Mediterranean against their will. It is the first study to examine the social, cultural and political ramifications of this late medieval trade in Greeks. The book’s wide geographical horizons and its accessible style ensure that it will appeal to anyone interested in the medieval Mediterranean or the history of slavery. Its use of previously unpublished or little-known textual sources and its extensive synthesis of Byzantine, Latin European and Islamic sources and scholarship ensure that it will offer new perspectives and revelations for the specialist.